Studi Perubahan Karakteristik Hidrologi (Debit Puncak dan Waktu Puncak) Akibat Perubahan Tata Guna Lahan di DAS Lesti dan DAS Gadang Kabupaten Malang - Fathia, Ayasha; Limantara, Lily Montarcih; Wahyuni, Sri (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2021)
Greater Malang, East Java Province is one of a region with fastest growing population. The increasing amount of residential area in a limited area can occur ecosystem damage in a watershed, caused by decreasing catchment area. One of the affected hydrological characteristics was the increasing peak discharge at the watershed outlet. Therefore, the objective of this study is to understand the correlation between changes in land use and hydrological characteristics in Lesti and Gadang Watershed. Sets of hourly rainfall and discharge (2014-2018), topographic maps, watershed maps, and land use maps are used in this study. Calculations analysis are operated by Microsoft Excel and ArcGIS 10.3 software. The results of land use are classified into dry forest, industrial forest, shrubs, farm, settlement, dryland farming, paddy field, savanna, and airport. It has been mentioned that the final result of this study were the decreasing area of dry forest and the increasing amount of settlement, accordant with increment average discharge.